2014
DOI: 10.1016/j.adt.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine structures and Landé gJ-factors for n=2 states in beryllium-, boron-, carbon-, and nitrogen-like ions from

Abstract: Energy levels, hyperfine interaction constants, and Landé g J -factors are reported for n = 2 states in beryllium-, boron-, carbon-, and nitrogen-like ions from relativistic configuration interaction calculations. Valence, core-valence, and corecore correlation effects are taken into account through single and double-excitations from multireference expansions to increasing sets of active orbitals. A systematic comparison of the calculated hyperfine interaction constants is made with values from the available l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 48 publications
2
21
3
Order By: Relevance
“…In Table VIII, we include previous results for the total g factor of B-like ions from Refs. [38,39,74,75]. Our results confirm the calculations of Refs.…”
Section: Contributionsupporting
confidence: 92%
“…In Table VIII, we include previous results for the total g factor of B-like ions from Refs. [38,39,74,75]. Our results confirm the calculations of Refs.…”
Section: Contributionsupporting
confidence: 92%
“…The uninterrupted developments of computational methodologies [1][2][3], together with the growing computational resources at the disposal of atomic physicists, have increased tremendously the accuracy of atomic structure calculations in the past decades [4][5][6][7][8][9][10][11]. Theoretical predictions of atomic properties have, therefore, become efficient tools to support the corresponding experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions can be improved with expansions that take into account the atomic property under investigation. Applications that have been extensively investigated are spectrum calculations for all levels up to a designated excited level, allowed and forbidden transitions [143,148,197,198,54], isotope shifts [199,200,201,184,202,203], hyperfine structures [204,159,205,206], nuclear effects on transition rates and spectra [26,207], magnetic field-induced transitions [208,209,20], to name a few. A comprehensive list of relativistic calculations and theoretical studies can be found in the RTAM bibliography database [210].…”
Section: Discussionmentioning
confidence: 99%